HUBUNGAN BEBAN KERJA FISIK, MENTAL, DAN KEBIASAAN SARAPAN TERHADAP TINGKAT KELELAHAN KERJA PADA KURIR EKSPEDISI PT POS INDONESIA KOTA SEMARANG - Medina Wardani Nasution; Baju Widjasena; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2021)
The role of human resources is very important to carry out work processes and achieve company goals. Companies need to pay attention to special skills or competencies to achieve goals. To produce optimal performance, human resources need protection in the form of occupational safety and health. To achieve this, companies need to pay attention to the factors that affect worker fatigue. The factors that influence worker fatigue come from two factors, namely internal factors (age, gender, nutritional status, health status, psychological state of the workforce), and external factors (workload and years of service, physical work environment). This study aims to analyze the relationship between physical workload, mental workload, and breakfast habits for PT. Pos Indonesia Semarang City. This research was a quantitative study using the coss sectional method. The instruments used were the IFRC Questionnaire to examine Work Fatigue, the NASA TLX questionnaire to examine mental workload and physical workload using workload measurements based on the level of Calorie Requirements. The population in this study were 121 employees. The sampling technique used was incidental sampling technique, namely the technique of determining the sample by chance, given the conditions that made it impossible to meet respondents directly during the pandemic, this technique was applied to anyone who was willing to fill out a questionnaire while still paying attention to the existing sample criteria. . Based on the results of the Spearman rank statistical test, it was found that there was no relationship between age (0.101> ρ value), physical workload (0.584> ρ value), and breakfast habits (0.982> ρ value) and work fatigue. However, there was a significant relationship between work fatigue on expedition couriers with their mental workload.